Overcoming Challenges in Lampung Language Instruction: A Study on Teaching Methods and Educational Technology Integration - Rachman, M Ridho; Zulfatussoraya, Eka Putri (Language, Technology, and Social Media, 2024)
The Lampung language, a regional language rich in cultural and historical significance, has seen a significant decline in usage among younger generations, primarily due to the influences of globalization and the increasing dominance of national and international languages. This study aims to thoroughly identify and analyze the challenges faced in teaching the Lampung language at the elementary school level (SDN), focusing on SDN 1 Tanjungsari Lampung Selatan. Employing a qualitative approach with a case study method, this research investigates both internal factors, such as curriculum design and teaching methodologies, and external factors, including parental and community support. The findings reveal several key challenges: the limited availability of engaging teaching materials, inadequate teacher training, and low student interest in learning the Lampung language. To address these issues, the study suggests developing interactive digital teaching resources and enhancing teacher training programs to improve pedagogical competencies. Furthermore, integrating technology and incorporating local cultural elements into the teaching process can potentially boost student interest and engagement. This approach not only aligns with modern educational practices but also promotes a deeper appreciation of local heritage. Ultimately, this research aims to contribute to the preservation efforts of the Lampung language, ensuring its continued relevance and vitality as an integral part of Indonesia's rich cultural tapestry. Through strategic educational interventions, the study hopes to inspire greater interest and participation among the younger generation, thereby safeguarding the linguistic and cultural legacy of the Lampung people.